2016
DOI: 10.1007/s10902-016-9717-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes with Age in Subjective Well-Being Through the Adolescent Years: Differences by Gender

Abstract: A one-year follow up study was conducted on a sample of 940 Spanish adolescents aged mostly from 10 to 15 in order to explore the extent to which their subjective well-being (SWB) changes from one year to the next, and whether these changes are the same for both genders regardless of the instrument used to measure SWB. Participants responded to the same four SWB scales twice, with an interval of a year in between. A decrease in the levels of SWB is identified from the years 11–12 onwards, the decrease in girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
146
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(179 citation statements)
references
References 44 publications
19
146
1
13
Order By: Relevance
“…() but is in congruence with Petito and Cummins (), Uusitalo‐Malmivaara (), and González‐Carrasco, Casas, Malo, et al. () follow‐up research when the latter used multi‐item scales. It also adds to the evidence that SWB as measured through multi‐item measures decreases sharply with age in Algeria, compared to Spain as indicated in Casas et al.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…() but is in congruence with Petito and Cummins (), Uusitalo‐Malmivaara (), and González‐Carrasco, Casas, Malo, et al. () follow‐up research when the latter used multi‐item scales. It also adds to the evidence that SWB as measured through multi‐item measures decreases sharply with age in Algeria, compared to Spain as indicated in Casas et al.…”
Section: Discussionsupporting
confidence: 69%
“…A longitudinal study in Spain (González‐Carrasco, Casas, Malo, Vinãs, & Dinisman, ) of 940 students aged 9–16, also conducted with a 1‐year interval, found significant decreases in overall SWB from the first to the second data collection in the majority of the studied cohorts. These decreases were more pronounced appeared from the age of 11 to 12 onwards and were more pronounced for girls than boys.…”
Section: Conceptualizations Of Well‐beingmentioning
confidence: 96%
“…Also in other studies supporting the findings of current research, life satisfaction, social support, and self-esteem were reported to have positive relationships with optimism [6,49]. Many studies conducted indicated to a significant relationship between subjective well-being and perceived social support [38,82,75,83,95]. Sayar [76] found significant relationships between teacher and peer support and psychological well-being and depression.…”
supporting
confidence: 83%
“…A review of studies conducted indicated that students receiving support by parents, school, and teachers had improved academic achievement and social relationships [40,74]. Social support predicted subjective well-being or life satisfaction [38,75,82]. Hence, it may be said that social support positively affects life satisfaction and subjective well-being.…”
Section: Introductionmentioning
confidence: 99%
“…González‐Carrasco, Casas, Malo, et al. (), based on results from longitudinal data, state that individuals’ set‐points change throughout their lifespan, as suggested by Mroczek and Spiro (), particularly during important biological and social transitions such as adolescence—hence the importance of considering the possibility that causes are not only environmental, but also developmental. In fact, Mroczek and Spiro (), using a nationally representative longitudinal annual panel study of Germans, found that 24% of respondents’ life satisfaction changed significantly from the first 5 years to the last 5 years of their study (from 1984 to 2000), with almost 9% of the sample changing an average of 3 or more points on a 10‐point scale.…”
Section: Growing Interest In the Decreasing‐with‐age Swb Tendencymentioning
confidence: 99%